Solidarity as Joint Action. - Sangiovanni, Andrea (Journal of Applied Philosophy, 2015)
The demand for social justice, especially in the context of the welfare state, is often framed as a demand of solidarity. But it is not clear why: in what sense, if any, is social justice best understood as a demand of solidarity? This article explores that question. There are two reasons to do so. First, very little has been written on the concept of solidarity, and almost nothing on why and how solidarity can both give rise to and be the target of a moral obligation. The first aim of the article is to fill this gap. The second aim of the article is to explore the normative implications of this account of solidarity for the commitment to social justice at the heart of the welfare state, and in so doing, to put into question the idea that shared experience or shared identity are either necessary or sufficient bases for social justice qua solidarity.